UJI EKSPERIMENTAL PEREDAM DI HILIR SLUICE GATE UNTUK PENGENDALIAN LONCATAN HIDRAULIK - Dyan Eka Nurhayati; Syamsuri (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2022)
A hydraulic jump can be formed by the discharge flowing through the sluice gate. This phenomenon occurred due the flow transformation from subcritic to supercritic. The hydraulic jump can cause an erosion in channel base. In this experimental study the stilling basin is planned in sluice gate downstream. The triangular, trapezoid, and sinusoidal stilling basin have been installed to control the flow and the hydraulic jump. The objective of this study is to evaluate the hydraulic jump in the sluice gate downstream, specifically the height and the jump length. This experimental study result can be used as consideration in designing a sluice gate. In this experimental study, comparisons were made on several models such as triangular stilling basin (model 1), trapezoidal stilling basin (model 2), and sinusoidal stilling basin (model 3), with the original design (Model 0). The modelling results were then evaluated by comparing to indicators such as sluice gate opening height (Y1), hydraulic jump height (Y2), and hydraulic jump length (Lj). The experimental study result exhibited that stilling basin in sluice gate downstream can reduce Y2 and Lj. The more roughness the stilling basin, the more effective to control the hydraulic jump. Y2 and Lj decreasing value from first to third experiment, that result also affects the length of transition part for the supercritic to subcritic flow. In this experimental study, the largest Y2 reduction efficiency was obtained on the Model 3, which the originally Y2 value was 0.11 m to 0.075 m. The result from this 31.82% efficiency is obtained 0.16 m of hydraulic jump length (Lj) and stilling basin length requirement (Ld) in 0.38 m.